Influence of viscosity and chemical composition of composite resins in non-carious cervical restorations: 12-month randomized clinical trial - Matos, Thalita; Josnei de Souza, Julian; Luján Méndez Bauer, María; Núñez Aldaz, Alejandra; Jardim Frossard Duarte, Luiza; Barceleiro, Marcos; Reis, Alessandra; Dourado Loguercio, Alessandro (Brazilian Dental Science, 2021)
Objective: The objective of this double-blind, randomized controlled clinical trial was to evaluate the clinicalperformance of two methacrylate-based flowable composite and ormocer-based flowable composite in non-cariouscervical lesions (NCCLs) of adult patients. Material and Methods: 183 restorations were performed on NCCLsusing the Futurabond U adhesive system, applied in the selective enamel etching mode in all cavities. After theadhesive application, the cavities were restored with one out of the three evaluated flowable composites (n = 61per group): ormocer-based flowable composite (Admira Fusion Flow, ORM), low viscosity methacrylate-basedcomposite (GrandioSO Flow, LV) and high viscosity methacrylate-based composite (GrandioSO Heavy Flow, HV).After 12 months of clinical performance, these restorations were evaluated according to FDI and USPHS criteriain the following items: retention/fracture, marginal adaptation, marginal staining, postoperative sensitivity andcaries recurrence. Results: eight restorations were lost/fractured after 12 months of clinical evaluation (1 inthe ORM and 7 in the HV group). The retention rates for 12- months (95% confidence interval) were 98.4%(91.3%-99.7%) for the ORM group, 100% (94.5%-100%) for the LV group and 88.5% (78.1%-94.3%) for theHV group, with no statistical difference identified between any pair of groups (p > 0.05). Five restorationspresented small marginal adaptation defects at the 12-months evaluation recall, and all of them were consideredclinically acceptable. Conclusion: The clinical performance of the universal adhesive associated to ormocer-basedor methacrylate-based flowable composite were found to be promising after 12-month of clinical evaluation.KEYWORDSDental bonding; Dental restoration; Clinical trial.